Hydrogen pipelines vs. HVDC lines: Should we transfer green molecules or electrons? - Aliaksei Patonia; Veronika Lenivova; Rahmatallah Poudineh; Christoph Nolden (The Oxford Institute for Energy Studies, 2023)
As the world races to decarbonize its energy systems, the choice between transmitting green energy as electrons through high-voltage direct current (HVDC) lines or as molecules via hydrogen pipelines emerges as a critical decision. This paper considers this pivotal choice and compares the techno-economic characteristics of these two transmission technologies. Hydrogen pipelines offer the advantage of transporting larger energy volumes, but existing projects are dwarfed by the vast networks of HVDC transmission lines. Advocates for hydrogen pipelines see potential in expanding these networks, capitalizing on hydrogen's physical similarities to natural gas and the potential for cost savings. However, hydrogen's unique characteristics, such as its small molecular size and compression requirements, present construction challenges. On the other hand, HVDC lines, while less voluminous, excel in efficiently transmitting green electrons over long distances. They already form an extensive global network, and their efficiency makes them suitable for various applications. Yet, intermittent renewable energy sources pose challenges for both hydrogen and electricity systems, necessitating solutions like storage and blending. Considering these technologies as standalone competitors belies their complementary nature. In the emerging energy landscape, they will be integral components of a complex system. Decisions on which technology to prioritize depend on factors such as existing infrastructure, adaptability, risk assessment, and social acceptance. Furthermore, while both HVDC lines and hydrogen pipelines are expected to proliferate, other factors such as market maturity of the relevant energy vector, government policies, and regulatory frameworks around grid development and utilization are also expected to play a crucial role. Energy transition is a multifaceted challenge, and accommodating both green molecules and electrons in our energy infrastructure may be the key to a sustainable future. This paper's insights underline the importance of adopting a holistic perspective and recognising the unique strengths of each technology in shaping a resilient and sustainable energy ecosystem.
Keywords: 330; decarbonization; electrolyser; energy transfer capacity; energy transfer infrastructure; HVDC lines; Hydrogen pipelines; Offshore wind; sustainable energy transition; system considerations; techno-economic analysis